Effectiveness of Village Fund in Encouraging Development and Reducing Poverty and Unemployment in Rural Area of Lampung Province - Irdham Riyanda; Elfindri Elfindri; Hefrizal Handra (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objective: The objective of this research is to find out the existence of village funds which are crucial to the financial resources of villages to develop their own regions. However, the existence and the amount of village funds which are distributed is not always in line to achieve the certain level of village development, reduce poverty and unemployment. Village Development is the 3rd Nawacita of the government, as well as a commitment of the government to recognize the existence of indigenous peoples.Methodology: The methodology used in this study is paired sample t-test and independent sample t-test by comparing the period before and after the distribution of village funds, for the condition in Lampung Province.Finding: The results of this study concluded that the existence of village funds, generally, has an effect to encourage village development. Even though in some areas this effect has not yet been shown.Conclusion: Further results also conclude that the existence of village funds has no effect on reducing poverty and unemployment of rural people. It is expected for the future to allocate and spend the village fund on activities which may directly reduce poverty and employment.